Does country with multi-ethnic, multi-linguistic and multi-religious society induce tourist arrivals? Worldwide evidence - Muzafar Shah Habibullah; Badariah Haji Din; Tan, Siow-Hooi (Penerbit Universiti Kebangsaan Malaysia, 2018)
The tourism sector contributes foreign exchange earnings to the nation; tax revenue to the government; and provide jobs to the population as well as open-up business opportunities to the communities. Thus, international tourist arrivals play a central role in stimulating economic growth by ensuring substantial export income in the form of international tourist expenditures to a destination country. A fundamental question that relates international visitors and the destination country is: “Does diversity play an important role in promoting tourism?” Studies have found that ethno-linguistic diversity affect a country’s tourism competitiveness negatively. This is because high levels of ethnic diversity tend to be associated with low investment, poor governance as a result of poor communication, low collective action and weak cohesion due to differences in ethnic groups’ value system. In this study, using a sample of 126 countries, our results suggest that ethnic, linguistic, and religious fractionalization negatively affected the destination choice of international tourist arrivals. Nevertheless, national income and safety of a country have positive impact on tourist arrivals, but air pollution affects negatively tourist arrivals to a destination country. Some policy implications that would promote tourism are that a country needs to promote and portray multi-racial country that are safe, peoples enjoy diversity in culture and lived in harmony; good facilities and infrastructure related to tourism; and less pollution.